Intestinal Helminth Infections Among Domesticated Cats in Malate, Manila, Philippines - Chan, Jan Michael; Flores, Mary Jane; Maghirang , Eligio Santiago; Chan, Helenar (Journal of Parasite Science, 2023)
Intestinal helminthiasis is a public health issue in developing nations particularly those which have insufficient access to clean water, sanitary infrastructures, and lacks public health education. Due to the zoonotic potential of some intestinal helminths, cats, and other mammalian species with direct contact to humans may act as reservoir hosts and provide a medium for the transmission of zoonotic infections. This study aimed to determine the prevalence of intestinal helminths among domesticated cats in Malate, Manila, Philippines. A total of 25 cat stools were collected, processed using Formol-Ether Concentration Technique (FECT) and were microscopically examined. The overall prevalence of intestinal helminths was 76% (19/25). The intestinal helminths identified include roundworms of phylum Nematoda: Toxocara cati (44%) and Ascaris spp. (20%), whipworm: Trichuris spp. (24%), and hookworm (12%). All of the identified intestinal parasites have zoonotic potential and domestic cats are significant reservoirs of zoonotic intestinal parasites that can facilitate the transmission of infection to humans. Therefore, an innovative one-health approach strategy which includes constant monitoring and control of stray and feral cats, access to potable water, public health education, and more sanitary infrastructures, can help resolve intestinal helminthiasis crisis in the Philippines.